Hot Off the Press: A Systematic Review And Meta‐analysis of Ketamine as an Alternative to Opioids for Acute Pain in the Emergency Department. (27th November 2018) - Heitz, Corey; Morgenstern, Justin; Bond, Christopher; Milne, William K.
Abstract: Ketamine has been studied as an alternative to opioids for acute pain in the emergency department setting. This review compares the effectives of intravenous ketamine at a dose of <0.5mg/kg to opioids for acute pain in adult patients. Measurements were taken within 60 minutes of administration. Ketamine was found to have similar effectiveness to opioids. Increased, but short‐lived, side effects were seen with ketamine.